Serum immunoglobulin levels in systemic lupus erythematosus: is IgA level an activity criterion (Annals of Medical Research, 2021)
None
Keywords: Systemic lupus erythematosus (SLE), Immunoglobulin A (IgA), Immunoglobulin G (IgG)